Chimeric Antigen Receptor-Redirected Regulatory T Cells Suppress Experimental Allergic Airway Inflammation, a Model of Asthma - Skuljec, Jelena; Chmielewski, Markus; Happle, Christine; Habener, Anika; Busse, Mandy; Abken, Hinrich; Hansen, Gesine (Frontiers in Immunology, 2017)
Cellular therapy with chimeric antigen receptor (CAR)-redirected cytotoxic T cells has shown impressive efficacy in the treatment of hematologic malignancies. We explored a regulatory T (Treg) cell-based therapy in the treatment of allergic airway inflammation, a model for asthma, which is characterized by an airway hyper-reactivity (AHR) and a chronic, T helper-2 (Th2) cell dominated immune response to allergen. To restore the immune balance in the lung, we redirected Tregs by a CAR towards lung epithelia in mice upon experimentally induced allergic asthma, closely mimicking the clinical situation. Adoptively transferred CAR Tregs accumulated in the lung and in trachea-bronchial lymph nodes, reduced AHR and diminished eosinophilic airway inflammation, indicated by lower cell numbers in the broncho-alveolar lavage fluid and decreased cell infiltrates in the lung. CAR Treg cells furthermore prevented excessive pulmonary mucus production as well as increase in allergen-specific IgE and Th2 cytokine levels in exposed animals. CAR Tregs were more efficient in controlling asthma than non-modified Tregs, indicating the pivotal role of specific Treg cell activation in the affected organ. Data demonstrate that lung targeting CAR Treg cells ameliorate key features of experimental airway inflammation, paving the way for cell therapy of severe allergic asthma.